Thalamic Volume Loss Is Greater in Children Than in Adults Following Middle Cerebral Artery Territory Arterial Ischemic Stroke. (October 2022) - Mastej, Emily J.; Leppert, Michelle H.; Poisson, Sharon; Ritchey, Zak; Barry, Megan; Rundek, Tatjana; Liebeskind, David S.; Mirsky, David; Bernard, Timothy J.; Stence, Nicholas V.
Background: Younger stroke patients may suffer worse outcomes than older patients; however, the extent to which age at stroke impacts remote areas of the brain remains unclear. The objective of this study was to determine thalamic volume changes ipsilateral to middle cerebral artery territory strokes based on age at acute ischemic stroke onset.Methods: Acute ischemic stroke patients <9 years, 9-18 years, and >18 years old were retrospectively recruited from a large quaternary care system. Each subject underwent an acute (<72 hours from AIS) and chronic (>90 days) magnetic resonance imaging (MRI) scan. Manual thalamic segmentation was performed.Results: Younger and older children had significantly greater stroke-side thalamic volume loss compared to adults (48.2%, P  = .022; 40.7%, P  = .044, respectively).Conclusions: Stroke-side thalamic volumes decreased across the age spectrum but to a greater degree in pediatric patients. This observation can affect functional and cognitive outcomes post stroke and warrants further research.